Identification of calcium and integrin-binding protein 1 as a reprogrammed glucose metabolism mediator to restrict immune cell infiltration in the stromal compartment of pancreatic ductal adenocarcinoma - Ma, Junrui; Song, Yue; Zhuang, Tongtao; Yang, Hao; Yang, Xiaobao; Zheng, Juanjuan; Luo, Jiajun; Xia, Yihan; Fei, Xuefeng; Chan, David W.; Wu, Di; Xu, Peiqing; et al. (Frontiers in Immunology, 2023)
An increasing body of evidence has suggested that reprogrammed metabolism plays a critical role in the progression of pancreatic ductal adenocarcinoma (PDAC) by affecting the tumor and stromal cellular components in the tumor microenvironment (TME). By analyzing the KRAS pathway and metabolic pathways, we found that calcium and integrin-binding protein 1 (CIB1) corresponded with upregulation of glucose metabolism pathways and was associated with poor prognosis in patients with PDAC from The Cancer Genome Atlas (TCGA). Elevated CIB1 expression combined with upregulated glycolysis, oxidative phosphorylation (Oxphos), hypoxia pathway activation, and cell cycle promoted PDAC tumor growth and increased tumor cellular com-ponents. Furthermore, we confirmed the mRNA overexpression of CIB1 and co-expression of CIB1 and KRAS mutation in cell lines from the Expression Atlas. Subsequently, immunohistochemistry staining from the Human Protein Atlas (HPA) showed that high expression of CIB1 in tumor cells was associated with an increased tumor compartment and reduced stromal cellular abundance. Furthermore, using multiplexed immunohistochemistry (mIHC), we verified that low stromal abundance was correlated with low infiltration of CD8+ PD-1− T cells which led to suppressed anti-tumor immunity. Overall, our findings identify CIB1 as a metabolic pathway-mediated factor for the restriction of immune cell infiltration in the stromal compartment of PDAC and highlight the potential value of CIB1 as a prognostic biomarker involved in metabolic reprogramming and immune modulation.